2016
DOI: 10.1080/13554794.2016.1264609
|View full text |Cite
|
Sign up to set email alerts
|

A case of musical anhedonia due to right putaminal hemorrhage: a disconnection syndrome between the auditory cortex and insula

Abstract: A 63-year-old, right-handed professional chorus conductor developed right putaminal hemorrhage, and became unable to experience emotion while listening to music. Two years later, neurological examination revealed slight left hemiparesis. Neuromusicological assessments revealed impaired judgment of "musical sense," and the inability to discriminate the sound of chords in pure intervals from those in equal temperament. Brain MRI and tractography identified the old hemorrhagic lesion in the right putamen and impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
1
12
0
1
Order By: Relevance
“…Despite a large population of brain‐damaged patients, only a single patient presented with a possible case of musical anhedonia. This individual had damage to the right hemisphere putamen and internal capsule, which is consistent with damage found in a prior case study …”
Section: Experimental Findingssupporting
confidence: 88%
See 4 more Smart Citations
“…Despite a large population of brain‐damaged patients, only a single patient presented with a possible case of musical anhedonia. This individual had damage to the right hemisphere putamen and internal capsule, which is consistent with damage found in a prior case study …”
Section: Experimental Findingssupporting
confidence: 88%
“…That is, a lack of pleasure in response to music, if due to a perceptual deficit, such as hearing loss or congenital amusia, would not be considered musical anhedonia. Neuropsychological studies have illustrated a double dissociation between musical reward and music perception; for example, case studies have identified individuals with severe deficits in music perception who still have rewarding responses to music, and case studies of patients with musical anhedonia illustrate preserved musical perceptual abilities …”
Section: Musical Anhedoniamentioning
confidence: 99%
See 3 more Smart Citations